The Global RAdical Cystectomy Evaluation and Management (GRACEM) pathway: single‐centre prospective observational cohort study protocol - Bruno Bernardini; Federico Piccioni; Manuele Pastore; Paolo Casale; NicolòMaria Buffi; Giovanni Lughezzani; Massimo Lazzeri; Alberto Saita; Maria Vittoria Fantacci; Stefano Mancon; Filipo Dagnino; Roberto Contieri; et al. (BJUI Compass)
Abstract Background Despite guideline recommendations, few institutions have implemented clinical pathways that incorporate frailty into routine decision‐making for patients undergoing radical cystectomy (RC). This paper presents an integrated clinical pathway designed to address the needs of frail patients undergoing RC. The purpose of the study is to determine whether a multifaceted prevention programme that tailors interventions to the syndromic components of frailty can improve postoperative morbidity and recovery time for patients. New insights will be gained into how to optimize the physical and mental status and quality of life of patients before and after surgery, up to 1 year later. Study design The Global RAdical Cystectomy Evaluation and Management (GRACEM) study is a prospective, observational, single‐centre, 2‐year cohort study. Patient enrolment began on 27 April 2023, and results are pending. Endpoints The primary endpoints are postoperative morbidity and the in‐hospital postoperative care burden. Postoperative morbidity is measured by the number of early (up to 1 month) and late (over 1 month and up to 12 months) complications, graded by severity according to the Clavien–Dindo classification. In‐hospital postoperative care burden is measured by the number and duration of key care processes as recorded by the Care Process Monitoring Chart, a tool developed for this study. Secondary endpoints are changes in frailty and health‐related quality of life (HRQoL) from pre‐intervention to planned follow‐up up to 1 year. Frailty is assessed with the Functional Limitations and Geriatric Syndromes Frailty Questionnaire (FLIGS‐FQ), another ad hoc tool. HRQoL is assessed using the EQ‐5D‐5L questionnaire combined with the cystectomy‐specific FACT‐Bl‐cys index from the first month of follow‐up. Patients and methods The GRACEM study includes patients with non‐metastatic, histologically confirmed, muscle‐infiltrating bladder cancer who underwent RC surgery with curative intent. This study is unique in that the GRACEM Core Team shares decision‐making throughout the pathway, from before the intervention to the end of the patient's follow‐up. The pathway involves the patient, family members and community services.